The effects of vertical separation and competition: evidence from US electric utility restructuring - Michael G. Pollitt; Jafar Sadeghi; Thomas Triebs (2024)
Competition usually increases firm productivity; but in network industries, effective competition requires vertical separation, which might reduce productivity and lead to a potential trade-off. We analyze the combined effect of competition and vertical separation on inefficient costs for US electricity industry restructuring. We estimate firm-level inefficiencies with the use of different nonparametric models of the technology and calculate net benefits with the use of difference-in-differences. The results depend on how we model the production technology and the length of the post-treatment horizon. The more flexible is the production frontier, the greater is the net benefit from divestiture and competition. Across our models the combined effect of divestiture and competition is positive.